Multicentre, randomised trial to investigate early nasal high—flow therapy in paediatric acute hypoxaemic respiratory failure: a protocol for a randomised controlled trial—a Paediatric Acute respiratory Intervention Study (PARIS 2) - Franz E Babl; Simon Craig; Ed Oakley; Meredith L Borland; Jocelyn Neutze; John F Fraser; Brenda Gannon; Kristen Gibbons; Shane George; Luregn J Schlapbach; Stuart Dalziel; Andreas Schibler; et al. (BMJ Open)
Introduction Acute hypoxaemic respiratory failure (AHRF) in children is the most frequent reason for non-elective hospital admission. During the initial phase, AHRF is a clinical syndrome defined for the purpose of this study by an oxygen requirement and caused by pneumonia, lower respiratory tract infections, asthma or bronchiolitis. Up to 20% of these children with AHRF can rapidly deteriorate requiring non-invasive or invasive ventilation. Nasal high-flow (NHF) therapy has been used by clinicians for oxygen therapy outside intensive care settings to prevent escalation of care. A recent randomised trial in infants with bronchiolitis has shown that NHF therapy reduces the need to escalate therapy. No similar data is available in the older children presenting with AHRF. In this study we aim to investigate in children aged 1 to 4 years presenting with AHRF if early NHF therapy compared with standard-oxygen therapy reduces hospital length of stay and if this is cost-effective compared with standard treatment.Methods and analysis The study design is an open-labelled randomised multicentre trial comparing early NHF and standard-oxygen therapy and will be stratified by sites and into obstructive and non-obstructive groups. Children aged 1 to 4 years (n=1512) presenting with AHRF to one of the participating emergency departments will be randomly allocated to NHF or standard-oxygen therapy once the eligibility criteria have been met (oxygen requirement with transcutaneous saturation <92%/90% (dependant on hospital standard threshold), diagnosis of AHRF, admission to hospital and tachypnoea ≥35 breaths/min). Children in the standard-oxygen group can receive rescue NHF therapy if escalation is required. The primary outcome is hospital length of stay. Secondary outcomes will include length of oxygen therapy, proportion of intensive care admissions, healthcare resource utilisation and associated costs. Analyses will be conducted on an intention-to-treat basis.Ethics and dissemination Ethics approval has been obtained in Australia (HREC/15/QRCH/159) and New Zealand (HDEC 17/NTA/135). The trial commenced recruitment in December 2017. The study findings will be submitted for publication in a peer-reviewed journal and presented at relevant conferences. Authorship of all publications will be decided by mutual consensus of the research team.Trial registration number ACTRN12618000210279